Pembentukan Biogas pada Media Eceng Gondok dengan Starter Kotoran Ternak - Kurniawan, Azhar Armia; Samani, Kurnia Abdullah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Animal manure and water hyacinth become waste if not used. One of its uses is as raw material for biogas. The purpose of this study was to determine the effect of the type of manure on the formation of biogas from water hyacinth as seen from: 1) the rate of biogas formation, 2) the temperature of the slurry, 3) the pH of the slurry, and 4) the weight of the biogas produced. Research with Completely Randomized Design (CRD) consisted of five treatments (P); P1: cow dung + water hyacinth + water, P2: buffalo dung + water hyacinth + water, P3: goat dung + water hyacinth + water, P4: horse dung + water hyacinth + water, and P5: broiler chicken dung + water hyacinth + water . Each treatment was repeated 4 times to obtain 20 experimental units. The composition of the raw material mixture consists of 8 kg of water hyacinth chopped 2 cm + 3 kg of livestock manure + 2 liters of water. Parameters observed were: rate of gas formation, slurry pH, slurry temperature, and weight of biogas produced. The research was conducted at the Biology Education Laboratory, Faculty of Teacher Training and Education, Kapuas Sintang University. Data were analyzed by ANOVA at 5% significance level using SPSS 16.0 and BNT test if there was a significant difference between treatments. The results showed that the type of manure only had a significant effect on the weight of biogas formed, but had no significant effect on the rate of biogas formation, slurry pH, and slurry temperature. Thus the five types of manure can be used as a starter in the manufacture of biogas made from water hyacinth.